2022
DOI: 10.1128/spectrum.00078-22
|View full text |Cite
|
Sign up to set email alerts
|

Mutation L319Q in the PB1 Polymerase Subunit Improves Attenuation of a Candidate Live-Attenuated Influenza A Virus Vaccine

Abstract: Vaccination represents the most effective strategy to reduce the impact of seasonal IAV infections. Although LAIV are superior in inducing protection and sterilizing immunity, they are not recommended for many individuals who are at high risk for severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…However, for some wild-type viruses, introduction of the full set of ts signatures from the cold-adapted AA virus was not enough to render the virus sufficiently attenuated; this depended mainly on the source of the PB2 gene [ 144 ]. Importantly, a recent study has found that the addition of a mutation L319Q in the PB1 protein significantly improved the attenuation of the H1N1pdm-based LAIV candidate carrying AA-specific attenuating mutations [ 145 ].…”
Section: Approaches To Improve the Performance Of Influenza Virus Vac...mentioning
confidence: 99%
“…However, for some wild-type viruses, introduction of the full set of ts signatures from the cold-adapted AA virus was not enough to render the virus sufficiently attenuated; this depended mainly on the source of the PB2 gene [ 144 ]. Importantly, a recent study has found that the addition of a mutation L319Q in the PB1 protein significantly improved the attenuation of the H1N1pdm-based LAIV candidate carrying AA-specific attenuating mutations [ 145 ].…”
Section: Approaches To Improve the Performance Of Influenza Virus Vac...mentioning
confidence: 99%